Relationship between sexism and marital satisfaction in Metropolitan Arequipa - Dianderas Cáceres, Carolina Margarita (2017)
The purpose of this study was to define the relationship between types of ambivalent sexism and marital satisfaction. Likewise, the influence of socio-demographic variables (age, gender and educational level) was related to the levels of sexism in order to identify possible causes of gender violence in the city of Arequipa. For this, a questionnaire was applied with the inventory of reagents of the ambivalent sexism of Glick & Fiske (1996) and of marital satisfaction of Pick & Andrade (1988) to a sample of four hundred people in the city of Arequipa metropolitan, between 16 and 74 years old. The results showed the independence of marital satisfaction from the levels of ambivalent sexism, but confirmed the existence of benevolent and hostile sexism in both men and women, the latter having the highest values of benevolent sexism. It was also found that there is more sexism among young people than in adults.